METHODOLOGY FOR CHECKING THE KNOWLEDGE OF STUDENTS IN INDEPENDENT EDUCATION THROUGH ARTIFICIAL INTELLIGENCE - Asadova Yulduz Ismatovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In this article, most users are increasing their knowledge by finding answers to their questions using software tools such as OpenAI ChatGPT, which consist of software tools such as OpenAI ChatGPT, can write code based on different programming languages and create standardized tests in a matter of seconds, We examined through AI software tools in order to determine to what extent students have mastered the science in order to assess independent educational topics that students have mastered using courses created by teachers on the basis of electronic platforms in the conditions of the modular-credit system, we planned to conduct an experimental test in order to compare students with their grades In such conditions, students who fully mastered the given subjects achieved a good result when they checked their knowledge through both systems.